Surgical Management of Acute Intersphincteric Paraproctitis - Agzamova Mahmuda Nabiyevna; Raximova Azizabonu Akmalovna; Akramova Iroda Abroljanovna (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Acute paraproctitis is a common inflammatory disease of the pararectal tissue in coloproctology. Specific Background: The intersphincteric variant is a severe form characterized by rapid infection spread within the intersphincteric space and risk of fistula formation. Knowledge Gap: Diagnosis remains challenging because patients often present with severe pain but minimal external perianal signs, leading to frequent misdiagnosis. Aims: This study examines the clinical features, diagnostic difficulties, and surgical management of acute intersphincteric paraproctitis based on literature review and clinical observations. Results: Patients commonly presented with severe anorectal pain and sphincter spasm, while body temperature often remained below 38 °C and external changes were minimal; several cases were initially misdiagnosed as hemorrhoids or anal fissure. Surgical treatment included abscess incision and drainage, excision of the internal opening, sphincter-preserving procedures, and minimally invasive methods such as LIFT and video-assisted techniques, with postoperative recovery and rare fistula formation during follow-up. Novelty: The study emphasizes distinctive clinical characteristics associated with diagnostic difficulty. Implications: Early recognition and standardized surgical approaches may reduce diagnostic errors and prevent chronic fistula development. Highlights: • Severe Anorectal Pain With Pronounced Sphincter Spasm Occurred Despite Minimal External Perianal Signs.• Diagnostic Errors Frequently Involved Misinterpretation as Hemorrhoids or Anal Fissure Before Specialized Examination.• Radical Surgical Intervention With Adequate Drainage Demonstrated Rare Fistula Formation During Follow-Up. Keywords: Acute Intersphincteric Paraproctitis, Surgical Management, Coloproctology, Anal Fistula Formation, Pararectal Inflammation.